Virgilian Incarnation: Hartman and the Issue of Auerbach’s Jewishness - de Graef, Ortwin (The Jewish quarterly review, 2013)
In his memoir A Scholar’s Tale, Geoffrey Hartman recognizes the decisive influence of Erich Auerbach, one of his teachers at Yale, on his own early work. Auerbach came to Yale after having spent the Second World War in Istanbul, where he wrote his magisterial Mimesis. That book not only bears the stamp of the war that was then ravaging Europe, the continent whose literary heritage he aimed to preserve in Mimesis, but also of a second trauma: the demise, somewhere (according to Auerbach) in between Dante and Montaigne, of a divinely sanctioned reality, which condemned the West to the historical world. For Auerbach, what saved this historical reality was the unfulfilled figure of the Incarnation still haunting it against all odds... The influence of Auerbach’s sense of lateness, and of the autumnal literary ethos it sustains, can be traced in Hartman’s lifelong engagement with William Wordsworth, whose exemplary remediation of the loss of rural life, Hartman recognizes, today threatens to fade away in our increasingly networked memory-and mediascapes. It is significant that in the last three decades, Hartman has supplemented his Romanticism and his work on the memory of the Holocaust with an increasingly explicit elaboration of the Jewish imagination. Does this point to the perceived insufficiency of Auerbach’s autumnal stance? Or does the tension between the literary, the disaster, and the religious point to an ethos beyond Incarnation?